PERFORMANCE OF STATE CIVIL SERVICES (ASN) BASED ON WORKLOAD AND ASSESSMENT OF WORK THE MINISTRY OF RELIGION IN DEPOK - Ratna Dumilah; Ading Sunarto (International Journal of Economy, Education and Entrepreneurship, 2022)
This study aims to determine the effect of Workload and work performance assessment partially and simultaneously on the performance of functional ASN teachers in the Ministry of Religion of Depok City. The research method used is descriptive quantitative. The population of this study amounted to 240 people, with the sample calculation using the Slovin formula to 150 samples used. Data collection techniques using observation techniques, interviews, and questionnaires. The data analysis technique used a validity test, reliability test, classical assumption test, multiple regression analysis, coefficient of determination, partial hypothesis test (T), and simultaneous hypothesis test (f). based on the study's results, the workload variable (X1) obtained a reliability value of 0.740. The partial test (T) has a value of tcount < ttable (1.736 < 1.97623) and strength by a significance value of 0.085> 0.05, then Ho1 is accepted, and H1 is rejected, meaning that the Workload does not have a partial effect on ASN performance. The work performance assessment variable (X2) results obtained a reliability value of 0.712. Partial test (t) obtained tcount > ttable (8.532>1.97623), strengthened by a significance value of 0.00 <0.05, then Ho2 reject, and H2 is accepted, meaning that the work performance assessment has a partial influence on ASN performance. And the Workload (X1) and work performance assessment (X2) on performance (Y) have a positive effect with the equation Y = 14 + 0.121X1 + 0.530X2. The value of determination is 0.485 or 48.5%. Simultaneous F test results, with a value of fcount,> ftable or (69.292 > 3.06), are also strengthened by a significance value of 0.00 < 0.05, then Ho3 is rejected, and H3 is accepted, meaning that the workload and work performance assessment have a simultaneous influence on the performance of functional ASN teachers in the Ministry of Religion of Depok City